APPLICATION OF US-SCS CURVE NUMBER METHOD AND GIS FOR DETERMINING SUITABLE LAND COVER OF SMALL WATERSHED - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study aims to reveal the appropriate land cover which can reduce runoff using US-SCS Curve Number method with GIS. Four land cover scenarios are developed to reveal which one of existing land cover types is appropriate for the area. To make a validation of the application US-SCS Curve Number Method, calculating observational run-off is required. Statistical analysis is than used to test those two run-off data. The result of this study shows that actual run-off depth is 2143, 0 mm and peak discharge is 91, 76 m3ls. The result also reveals thatforest coverage can reduce dramatically surface run-off until 48, 38 percent. Potato increases surface run-off 1, 59 percent, on the contrary, applying cacica papaya can reduce surface run-off 24, 6 percent. Scenario 4 is developed based on the result of the previous scenario on run-off yield Run-off yield resultfrom scenario 4 is 1690, 40 mm (decrease 21, 14 percent from actual run-off). Statistical analysis shows that there is no difference between observed run-off depth and estimated run-off depth in the level of significance 5 %.